Overview of Kenyan Government Initiatives in Slum Upgrading: The Case of KENSUP and KISIP Projects - Solymári, Dániel; Mangera, Janet; Czirják, Ráhel; Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
The goal of this paper is to explore the slum upgrading processes: the implementation of the Kenyan KENSUP project, associated successes and failures, and to draw possible lessons that can be learned from the initiative. The study utilized field work desk reviews to gather relevant information regarding slum upgrade processes in Kenya. The criteria used in the review process entailed exploring the context in which the KENSUP upgrading project was implemented, focusing on the legal frameworks, process of implementation, achievements, results, setbacks and failures in the processes in order to draw lessons for future programmes.